LPIC-2 cert guide - Brunson, Ross, 1965- (Cert guide., 2016)
This is the eBook version of the print title. Note that the eBook does not provide access to the practice test software that accompanies the print book. Learn, prepare, and practice for LPIC-2 201-400 and 202-400 exam success with this Cert Guide from Pearson IT Certification, a leader in IT Certification. Master LPIC-2 201-400 and 202-400 exam topics Assess your knowledge with chapter-ending quizzes Review key concepts with exam preparation tasks LPIC-2 Cert Guide (201-400 and 202-400 Exams) is a best-of-breed exam study guide. Expert Linux/Unix instructor William "Bo" Rothwell shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The book presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Review questions help you assess your knowledge, and a final preparation chapter guides you through tools and resources to help you craft your final study plan. Well-regarded for its level of detail, assessment features, and challenging review questions and exercises, this study guide helps you master the concepts and techniques that will enable you to succeed on the exam the first time. The study guide helps you master all the topics on both LPIC-2 exams, including: Capacity planning Managing the kernel Managing system startup Managing filesystems and devices Administering advanced storage devices Configuring the network Performing system maintenance Administering Domain Name Server (DNS) Configuring web services Administering file sharing Managing network clients Administering e-mail services Administering system security.